Formation of a Programming Languages Stack and a methodology of teaching to students specialized in Computer Science at Technical Universities in the context of interdisciplinarity - Korotenko, Gregory; Korotenko, Leonid (Technium Sustainability, 2021)
Rapid development of the computing hardware and software components has created many new technological directions for the use of computer tools. Thus, information, digital and end-to-end technologies for the processing of a variety of data exist and are developing, as well as many different types of platforms for their support, including digital platforms. At the same time, the active development of computing and its sub-disciplines directly impacts on the programming languages used in this area. This article attempts to assess the range of the most important and frequently used programming languages for the formation of a stack thereof and the methodology of their teaching in the context of the interdisciplinarity of modern computer specialties at technical Universities. Youtube link: https://youtu.be/12PMVGtPfnU